KEARIFAN LOKAL SUKU BADUY DALAM PEMANFAATAN MADU SEBAGAI HASIL HUTAN BUKAN KAYU DI DESA KANEKES KECAMATAN LEUWIDAMAR KABUPATEN LEBAK PROVINSI BANTEN - Syam, Waridat Ilahiyat; M, Iskandar A; Tavita, Gusti Eva (JURNAL HUTAN LESTARI, 2020)
Lots of local wisdom with local people. In other words, local wisdom can be implemented as ideas, values, local views that are wise, full of wisdom, good value, which are embedded and followed by members of the community. Therefore, local wisdom can be defined as noble values contained in local cultural assets, in the form of traditions, ideas, and life motto. The Baduy community in Kanekes Village, Leuwidamar Subdistrict, is one of the tribes in Indonesia which until now still maintains the values of local wisdom that they have and believe in, amidst the advancement of civilization around them. Research on the local wisdom of the Baduy Tribe in Kanekes Village, Leuwidamar Subdistrict, Lebak Regency, Banten Province aims to see the local wisdom of the Baduy Tribe in utilizing forest resources by the Baduy tribe for the sustainable use of non-timber forest products in the form of forest honey. The types of data taken in this study are primary data and secondary data. Primary data was obtained from the results of interviews with the community in the Baduy Tribe, Kanekes Village, Leuwidamar District, Lebak Regency, Banten Province, Banten Province. Secondary data were complementary data obtained from references which included general conditions of the location, socio-cultural conditions, activities and others. The research was conducted using the snowball sampling method and also using a qualitative descriptive method fpr compiling the result of the research on local wisdom of the baduy tribe.Keyword: Baduy Tribal, Forest Honey, Local Wisdom